Assessment of malocclusion pattern in Bangladeshi Population - Rubby, Md Golam; Sultana, Nihar; Jannath, Fatema; Hassan, Gazi Shamim (Update Dental College Journal, 2020)
Background: Malocclusion is one of the most common dental problems together with dental caries, gingival disease, dental fluorosis which varies in different part of the world among different populations. The aim of this study was to assess the malocclusion pattern in Bangladeshi population to provide quantitative information regarding the pattern of dentofacial characteristics. Methods : This cross sectional study was carried out with the orthodontic records of 256 patients who attended and treated in the Department of Orthodontics ,Bangabandhu Sheikh Mujib Medical University (BSMMU) Hospital , Dhaka. Malocclusion pattern mainly assessed by Angle’s classification system; along with incisor classification system other variables like overjet, overbite, cross bite ,crowding, spacing and median diastema were recorded. Finally data were analyzed by using SPSS software (Version 21). Results : The study result showed out of 256 orthodontic patients majority (68.7%) were female, in Angle’s classification Class I malocclusion was the most prevalent (55.5%) type of malocclusion followed by Class II (38.3%) and Class III (6.3%). The most prevalent malocclusion trait found crowding (67.7%), followed by increase overjet (65.6%), increase overbite or deep bite (50.4%); the least prevalent malocclusion trait found scissor bite (1.2%) followed by posterior cross bite (5.1%) and median diastema (12.5%). Statistical significant relationship observed in the distribution of malocclusion by Angle’s classification with sex ( as p value < .05). Conclusion: This hospital based study concludes that in Angle’s classification system: Class I malocclusion was prevalent along with the malocclusion trait crowding, which actually gives a general idea about the malocclusion pattern in Bangladeshi population. Update Dent. Coll. j: 2020; 10 (2): 14-17